2011
DOI: 10.1038/ejcn.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Are infants born in baby-friendly hospitals being exclusively breastfed until 6 months of age?

Abstract: Background/Objectives: To objectively measure rates of breast-feeding to infants born in a baby-friendly hospital in Bangalore, India, and to capture home-based compliance to exclusive breastfeeding (EBF). Subjects/Methods: Breast-milk (BM) and non-breast-milk (NBM) water intake were assessed in 50 mother-infant pairs using a deuterium dilution technique at months 1, 3 and 6. Results: Complementary feeding (CF) was introduced as early as 1 month among 44% of the infants, and only 14.2% remained as exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 17 publications
(16 reference statements)
4
37
0
Order By: Relevance
“…These finding are corroborated by studies in other countries [132,133]. In India, persistent crying in infants was found to be a barrier to EBF and, in Iran, low birth weight was reported to lead to a low rate of breastfeeding [132,133].…”
Section: Discussionsupporting
confidence: 76%
“…These finding are corroborated by studies in other countries [132,133]. In India, persistent crying in infants was found to be a barrier to EBF and, in Iran, low birth weight was reported to lead to a low rate of breastfeeding [132,133].…”
Section: Discussionsupporting
confidence: 76%
“…1,2 We are in agreement with the author's viewpoint that the lack of commitment to implement the 10 steps of the Baby-Friendly Hospital Initiative, and specifically those that require staff skills and time may be the key reason why early complementary feeding is observed even in baby-friendly hospitals (BFH) and that these deserve special mention. Our study, which objectively assessed the compliance to exclusive breastfeeding (EBF), drew the same conclusion, and objectively showed that even BFH may not necessarily have improved rates of EBF.…”
supporting
confidence: 65%
“…We read with great interest the article by Samuel et al 1 The authors found that in spite of being delivered in a baby-friendly hospital (BFH) early complementary feeding (CF) was observed at home. Based on their findings, they suggested home-and communityoriented approaches to improve exclusive breast feeding rates.…”
mentioning
confidence: 89%